Daily activity rhythm of the African stingless bee Hypotrigona gribodoi (Hymenoptera: Meliponini) in the dry season, with notes on nest structure and colony composition - Asante, Prince; Starr, Christopher K. (Journal of Melittology, 2024)
We studied 18 colonies of Hypotrigona gribodoi (Magretti) nesting in the tubing of a disused horticultural sprinkler system during the late dry season in Ghana, West Africa. Flight activity began around dawn (about 06:00), rising to a peak in the half-hour starting 07:30 and gradually declining to end around dusk (about 18:00). Bees returning with pollen showed a more extended peak from 07:30 to 09:00. Dissection of 18 nests showed a mean inner volume of 466.5 ml, while 17 active colonies had a mean number of 851 adults. Colony size is positively correlated with nest size. It is likewise positively correlated with the fraction of fully mature adult females. Several nests had branching entrance tubes with an angle of roughly 30⁰ between branches. In each of three such nests studied, there was a marked division in the use of the two branches, such that one served mainly as an exit and the other as an entrance.